2015
DOI: 10.1509/jmr.13.0415
|View full text |Cite
|
Sign up to set email alerts
|

Harbingers of Failure

Abstract: We show that some customers, whom we call 'Harbingers' of failure, systematically purchase new products that flop. Their early adoption of a new product is a strong signal that a product will fail -the more they buy, the less likely the product will succeed. Firms can identify these customers either through past purchases of new products that failed, or through past purchases of existing products that few other customers purchase. We discuss how these insights can be readily incorporated into the new product d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…When estimating the effect of public school quality on residential choices, [15] controls for neighborhood unobservables by using the residential choices of people without school-age children. [1] and [55] use purchases of a certain group of consumers as a predictor of new product failures in various categories.…”
Section: Discussion: Benefits Of Identifying Product Valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…When estimating the effect of public school quality on residential choices, [15] controls for neighborhood unobservables by using the residential choices of people without school-age children. [1] and [55] use purchases of a certain group of consumers as a predictor of new product failures in various categories.…”
Section: Discussion: Benefits Of Identifying Product Valuesmentioning
confidence: 99%
“…I assume that consumers are myopic, i.e., they maximize the current-period predicted consumption utility. 1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of almost 9,000 new products that achieved broad distribution at a national retailer revealed that just 40% of them were still sold three years later. 1 Some of these products did not create value for customers and deserved to fail. However, some of them would have created value if customers had adopted them.…”
Section: Why Great Products Failmentioning
confidence: 99%